A corpus-based study on the use of phrasal verbs in Malaysian secondary school textbooks - Md. Zamin, Ainul Azmin; Elfeky, Mahmoud; Kamarudin, Rafidah; Abdul Majid, Faizah (Australian International Academic Centre PTY.LTD., 2019)
Phrasal verbs (PVs) are one of the most notoriously puzzling aspects of English language instruction. Despite their difficulty and idiosyncrasies, they are of high relevance for ESL/EFL learners because mastery of PVs is often equated with language proficiency. Different from prior researches, this content analysis study seeks to identify the PVs used in the Malaysian upper secondary school textbooks and the frequency count of each PV in each textbook using a corpus linguistic approach. The most frequently PVs in each textbook were compared to the list provided by Biber et al (1999)’s Longman Grammar of Spoken and Written English corpus. Findings from this study revealed that the selection and presentation of these combinations in the secondary school textbooks used in Malaysia depended more on authors’ intuition rather than on empirical findings and pedagogical principles. There were no clear explanations of Phrasal Verbs in both textbooks that were analysed. Despite the large number of PVs in the corpus, their presentation in the textbooks was far from satisfactory with some being over-repeated at the expense of some others. This paper makes a few suggestions to further improve the present treatment of PVs in the textbooks used at upper secondary schools in Malaysia. It is suggested that accurate definitions and appropriate selection and presentation of PVs should be considered. Rather than relying on intuition, Malaysian textbook writers must consider integrating the use of corpus into their selection of PVs to be presented to students